Increased BST2 expression during simian immunodeficiency virus infection is not a determinant of disease progression in rhesus monkeys. Issue 1 (December 2015) - Mussil, Bianka; Javed, Aneela; Töpfer, Katharina; Sauermann, Ulrike; Sopper, Sieghart
Abstract Background Bone marrow stromal cell antigen 2 (BST2), also known as tetherin, HM1.24 or CD317 represents a type 2 integral membrane protein, which has been described to restrict the production of some enveloped viruses by inhibiting the virus release from the cell surface. This innate antiviral mechanism is counteracted by the HIV-1 viral factor Vpu, targeting BST2 for cellular degradation. Since antiviral BST2 activity has been mainly confirmed by in vitro data, we investigated its role in vivo on the disease progression using the SIV/macaque model for AIDS. We determined BST2 expression in PBMC and leukocyte subsets of uninfected and SIV-infected rhesus macaques by real-time PCR and flow cytometry and correlated it with disease progression and viral load. Results Compared to pre-infection levels, we found increased BST2 expression in PBMC, purified CD4+ lymphocytes and CD14+ monocytes of SIV-infected animals, which correlated with viral load. Highest BST2 levels were found in progressors and lowest levels comparable to uninfected macaques were observed in long-term non-progressors (LTNPs). During acute viremia, BST2 mRNA increased in parallel with MX1, a prototype interferon-stimulated gene. This association was maintained during the whole disease course. Conclusion The detected relationship between BST2 expression and viral load as well as with MX1 indicate a common regulation by the interferon response and suggest rather limited influence of BST2 in vivo on the disease outcome.